An efficient synthesis of novel sucrose-containing dilactams - Potopnyk, Mykhaylo A. (Monatsh Chem, 2013)
ABSTRACT: An efficient and convenient approach to sucrose-containing dilactams has been developed. The method, based on reaction of regioisomeric 6,6′-di-O-[(aminomethyl)-phenyl]-1′,2,3,3′,4,4′-hexa-O-methylsucrose with isophtaloyl or 2,6-pyridinedicarbonyl dichlorides, provided the 1:1-macrocycles in good yields. GRAPHICAL ABSTRACT: [Image: see text].